Enhancement of biological oxygen demand detection with a microbial fuel cell using potassium permanganate as cathodic electron acceptor. (15th December 2019) - Wang, Siqi; Tian, Shuai; Zhang, Panyue; Ye, Junpei; Tao, Xue; Li, Fan; Zhou, Zeyan; Nabi, Mohammad
Abstract: When dual-chamber microbial fuel cell (MFC) is used to detect biochemical oxygen demand (BOD), dissolved oxygen is traditionally used as cathodic electron acceptor. The detection limit of this MFC-based BOD biosensor is usually lower than 200 mg/L. In this paper, the startup of MFC-based BOD biosensor was researched and the external resistor of MFC was optimized. Results showed that the MFC started up with the dissolved oxygen as cathodic electron acceptor within 10 d, and the external resistor was optimized as 500 Ω to ensure the maximum output power of MFC. Dissolved oxygen and potassium permanganate (KMnO4 ) were used as cathodic electron acceptor to run MFC for detection of wastewater BOD, and the performances of two kinds of BOD biosensors were compared. The MFC-based BOD biosensor using KMnO4 (10 mmol/L) as cathodic electron acceptor exhibited an excellent performance, compared with that using dissolved oxygen. The upper limit of BOD detection was greatly broadened to 500 mg/L, the response time was shortened by 50% for artificial wastewater with a BOD of 100 mg/L, and the relative error of BOD detection was reduced to less than 10%. The MFC-based BOD biosensor using KMnO4 as cathodic electron acceptor showed a better linear relationship (R 2  > 0.992) between the electric charge and BOD concentration within a BOD range of 25–500 mg/L. The MFC-based BOD biosensor using the KMnO4 as cathodic electron acceptor is promising with a better application prospect. Graphical abstract: Image 1 Highlights: MFC-based BOD biosensor (KMnO4 as electron acceptor) showed a better performance. Upper detection limit of BOD detection was greatly broadened to 500 mg/L. Relative error of BOD detection was reduced to less than 10%.